The Impact of Intraparty Electoral Reforms on Party System Nationalization. Issue 2 (7th December 2017) - Riera, Pedro
Abstract: Abundant research demonstrates that electoral rules have an impact on party system fragmentation. Building on these findings, and adopting a dynamic approach, this article investigates the effect of changes of the ballot structure on party system nationalization and shows that this effect is conditioned by levels of ethno-geographic concentration and political decentralization. Specifically, candidate-centered reforms hamper party system nationalization by making parties less likely to obtain similar vote shares across constituencies, whereas party-centered reforms tend to foster it. Moreover, concentration of ethnic groups at the district level or considerable political decentralization exacerbates the impact of candidate-centered changes. These effects are demonstrated through an analysis of an original dataset of electoral reforms and party system nationalization as measured with different indices across fifty-nine democracies and more than five hundred legislative elections.